HIF-1 and SKN-1 coordinate the transcriptional response to hydrogen sulfide in Caenorhabditis elegans. - Dana L Miller; Mark W Budde; Mark B Roth (PLoS ONE, 2011)
Hydrogen sulfide (H₂S) has dramatic physiological effects on animals that are associated with improved survival. C. elegans grown in H₂S are long-lived and thermotolerant. To identify mechanisms by which adaptation to H₂S effects physiological functions, we have measured transcriptional responses to H₂S exposure. Using microarray analysis we observe rapid changes in the abundance of specific mRNAs. The number and magnitude of transcriptional changes increased with the duration of H₂S exposure. Functional annotation suggests that genes associated with protein homeostasis are upregulated upon prolonged exposure to H₂S. Previous work has shown that the hypoxia-inducible transcription factor, HIF-1, is required for survival in H₂S. In fact, we show that hif-1 is required for most, if not all, early transcriptional changes in H₂S. Moreover, our data demonstrate that SKN-1, the C. elegans homologue of NRF2, also contributes to H₂S-dependent changes in transcription. We show that these results are functionally important, as skn-1 is essential to survive exposure to H₂S. Our results suggest a model in which HIF-1 and SKN-1 coordinate a broad transcriptional response to H₂S that culminates in a global reorganization of protein homeostasis networks.